Prehabilitation program for coronary artery bypass grafting patients and perioperative myocardial injury. (11th May 2021) - Argunova, Y; Belik, E; Moskin, E; Gruzdeva, O; Pomeshkina, S; Barbarash, O
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose: To evaluate morphological and functional cardiac parameters and to assess changes in markers of perioperative myocardial injury in patients undergoing different prehabilitation program before elective coronary artery bypass grafting (CABG). Methods: 60 male patients with stable coronary artery disease (CAD) underwent screening in the preoperative period and were randomized into two groups. Group 1 (n = 30, mean age 61.5 [56; 63]) underwent supervised treadmill exercises at intensity corresponding to 80% of VO2 peak during the preoperative management. Group 2 (n = 30, mean age 62.0 [56; 64]) patients did not undergo any additional trainings. Patients underwent a standard echocardiographic (ECHO-CG) study in the preoperative period and at days 5-7 after CABG. Serum markers of myocardial injury (troponin I, NT-proBNP) were measured in both groups of patients in the preoperative period before training (point 1), at the end of exercise training session (point 2) and at days 5-7 (point 3) after CABG. Results: Left ventricular end-systolic dimension (p = 0.039) and left ventricular end-systolic volume (p = 0.039) increased by 8.5% and 18% in patients who underwent supervised exercise trainings as compared to the baseline values. An increase in these parameters was more pronounced in the control group (17% (p = 0.00029) and 41% (p = 0.00028), respectively). Both groups were comparable in troponin I levels at three study points. Troponin I values were within the reference range. NT-proBNP levels showed a downward trend in patients with prehabilitation at the end of the training sessions, while in the control group NT-proBNP levels increased. An increase in NT-proBNP levels was reliable in patients without exercise trainings (p = 0.003) after CABG compared to the preoperative values. However, changes in NT-proBNP levels were insignificant in patients who underwent prehabilitation (p > 0.05). Conclusion: The safety of high-intensity exercise trainings in the prehabilitation program for CABG had been confirmed by laboratory markers indicative for myocardial injury. The obtained data proved the efficiency of active prehabilitation for optimizing morphological and functional cardiac parameters as well as inducing cardioprotection.